2023
DOI: 10.3390/cimb45050246
|View full text |Cite
|
Sign up to set email alerts
|

HTRA1 in Placental Cell Models: A Possible Role in Preeclampsia

Abstract: The HtrA serine peptidase 1 (HTRA1) is a multidomain secretory protein with serine–protease activity involved in the regulation of many cellular processes in both physiological and pathological conditions. HTRA1 is normally expressed in the human placenta, and its expression is higher in the first trimester compared to the third trimester, suggesting an important role of this serine protease in the early phases of human placenta development. The aim of this study was to evaluate the functional role of HTRA1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They found that HTRA1 expression was increased in an oxidative stress condition, which is typical in women who developed late PE. Moreover, the HTRA1 contribution in cell migration and invasion was shown, underlining the possible role of HTRA1 in placental development and, consequently, in PE onset [ 101 ]. The correlation between this protein and adverse pregnancy outcomes has recently emerged.…”
Section: Protein Placental Biomarkersmentioning
confidence: 99%
“…They found that HTRA1 expression was increased in an oxidative stress condition, which is typical in women who developed late PE. Moreover, the HTRA1 contribution in cell migration and invasion was shown, underlining the possible role of HTRA1 in placental development and, consequently, in PE onset [ 101 ]. The correlation between this protein and adverse pregnancy outcomes has recently emerged.…”
Section: Protein Placental Biomarkersmentioning
confidence: 99%
“…Reduced arterial compliance and peripheral vasoconstriction characterize the preeclamptic condition from the early stages [16]; however, the exact pathophysiology of preeclampsia is still unknown. Probably, the initial defect in placentation and vascularization in the placenta bed due to poor trophoblast invasion of the spiral arteries [17][18][19] leads to an inappropriate activation of the immune system [20], as it occurs in recurrent miscarriage [21]. It is known that oxidative stress and inflammation are involved in endothelial dysfunction [22][23][24][25][26][27], a key process underlying several diseases including preeclampsia [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%